The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cncr.31858
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive effects of endocrine therapy in survivors of breast cancer: A prospective longitudinal study up to 6 years after treatment

Abstract: BACKGROUND: After treatment of primary breast cancer, endocrine therapy (ET) is prescribed for patients with hormone receptor-positive cancers. Despite ET recommendations of 5 to 10 years of treatment, to the authors' knowledge there is little prospective study of its impact on cognitive function over an extended period of time. ET has known pharmacologic effects on the brain. Cognitive side effects are a concern for many women, with mixed findings reported in various studies. The current prospective longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
1
33
0
5
Order By: Relevance
“…There are mixed data on the cognitive effects of ET (Table IV). In the recently published prospective longitudinal Mind Body Study, Van Dyk et al (17) reported on the complex long-term effects of ET on neuropsychological functions (17). The analysis was based on both neuropsychological testing and self-reported data in 189 BC patients among which follow-up was extended to 3-6 years in 102 participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are mixed data on the cognitive effects of ET (Table IV). In the recently published prospective longitudinal Mind Body Study, Van Dyk et al (17) reported on the complex long-term effects of ET on neuropsychological functions (17). The analysis was based on both neuropsychological testing and self-reported data in 189 BC patients among which follow-up was extended to 3-6 years in 102 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Across most domains, there was similar improvement in both groups during the years of follow-up. The significance of these results is justified by the large number of patients, long follow-up in more than half of the cases, complex methodology in various domains and careful statistical analysis; the design of the follow-up lowered practice effects (17). Nevertheless, the confounder effects of chemotherapy (about half of the patients in both groups received chemotherapy <3 months within entering the study), varying ET and menopausal status were not excluded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations